Effect Perception About Teachers Competency And Learning Creativities For Studentâs Accounting Learning Achievement XII IPS SMA Pertiwi 2 Padang - Astutik, Tri - (Pendidikan Ekonomi, 2014)
The purposes of this research are: 1) studentsâ perception about teachers competency toward studentsâ accounting learning achievement XII IPS at SMA Pertiwi 2 Padang, 2) the effect of learning creativities toward studentsâ accounting learning achievement XII IPS at SMA Pertiwi 2 Padang. 3) the effect of studentsâ perception about teachers competency and creativities toward studentsâ accounting learning achievement XII IPS at SMA Pertiwi 2 Padang. The kinds of this research used associative research was causal. The population of this research was all of the students XII IPS at SMA Pertiwi 2 Padang about 102 students. In choosing the sample, the researcher used simple random sampling about 81 students. The technic of data analysis: descriptive analysis, inductive analysis. The result of this research were: 1) there were positive and significance effect of studentsâ perception about teachers competency toward studentsâ accounting learning achievement XII IPS at SMA Pertiwi 2 Padang, which is indicated by the value of the coefficient of 0,138. Value of this coeffisient is significant because tcount 2,094 > ttable 1,664 with significant value 0,039 < a=0,05, then reject H0 and accept Ha. It means that if the studentsâ perception about teachers competency was good, it would be better to studentsâ accounting learning achievement. 2) there were positive and significance effect of learning creativities toward studentsâ learning learning accounting achievement XII IPS at SMA Pertiwi 2 Padang, which is indicated by the value of the coefficient of 0,562. Value of this coeffisient is significant because tcount 6,349 > ttable 1,664 with significant value 0,000 < a=0,05, then reject H0 and accept Ha. It showed that if the students have high creativities, it increased studentsâ accounting learning achievement XII IPS at SMA Pertiwi 2 Padang. 3) there were positive and significance effect between studentsâ perception about teachers competency and creatvities toward studentsâ accounting achievement XII IPS at SMA Pertiwi 2 Padang, which is indicated by the value of Fcount 103,797 > Ftable 3,11 with significant value 0,000 < a=0,05. It showed that studentsâ perception about teachers competency and creativities were good. So, it would be better to studentsâ accounting learning achievement.